Eschatologiczna nagroda w pismach Tertuliana - Wysocki, Marcin (Vox Patrum, 2008)
Tertullian (ca. 155-225) very often is described as a rigorist, who is burning with vengeance. Although for him the coming end is above all a time of reckoning., in his writings, as „the theologian of the hope” - as Erie Osborn has called him - a lot of thoughts about future reward can be found. In this paper the Tertullian’s teaching about eschatological reward is presented. Among his ideas of the future life the idea of resurrection of the body is found as the most important. And as the result of it Tertullian amplifies his teaching about heaven, as the being with God and Christ, as the banquet in the Kingdom of God. According to Tertullian it will be one reward - eternal life - but in different characters. The special place in his system of eschatological reward is granted to martyrs.